The Peculiarities of Iris Murdoch’s artistic method (based on her novel “The Black Prince”) - Telegina, N.; Butsyak, T. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
For the purpose of defining Iris Murdoch’s artistic method a complex investigation of the problems and style of her famous novel “The Black Prince” was made. Special attention was given to the philosophical problems of Good and Evil, Contingency and Necessity in human life, absurdity, choice, aloofness, to the philosophical aspect of the novel, which is revealed with the help of the flash-back technique. The problems raised in the novel, its sensitive main character absorbed in psychoanalysis and looking for the sense of existence, naturalistic details & the postscripts, revealing different subjective points of view on the same events, prove that the novel should be regarded as existentialist